Resource Misallocation Among Listed Firms in China : The Evolving Role of State-Owned Enterprises - Jurzyk, Emilia; Ruane, Cian. (Washington, D.C. : International Monetary Fund, 2021)
We document that publicly listed Chinese state-owned enterprises (SOEs) are less productive and profitable than publicly listed firms in which the state has no ownership stake. In particular, Chinese listed SOEs are more capital intensive and have a lower average product of capital than non-SOEs. These productivity differences increased between 2002 and 2009, and remain sizeable in 2019. Using a heterogeneous firm model of resource misallocation, we find that there are large potential productivity gains from reforms which could equalize the marginal products of listed SOEs and listed non-SOEs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet